Mars – a target for teachers and science students. Issue Volume 15:Issue S367(2019) (December 2019) - Sundin, Maria; Bernhardt, Peter; Ekberg, Peter; Enger, Jonas; Johnsson, Andreas
Abstract: An interdisciplinary course about Mars for teachers and science students is presented. The focus of the course is on planning for a journey with humans to the planet Mars. Issues in ethics, morality, rights and obligations, conflict management and human psychology as well as rocket orbits, fuel economy, radiation hazards and knowledge of the solar system are included. Examination of the teacher students include interpretation of the course material for future pedagogical usage.